Highly sensitive optical thermometer based on FIR technique of transparent NaY2F7:Tm3+/Yb3+ glass ceramic - Chen, SunYueZi; Song, WeiHui; Cao, JiangKun; Hu, FangFang; Guo, Hai (Journal of alloys and compounds, 2020)
Non-contact temperature sensors based on up-conversion photoemission with quick response and in situ monitoring exhibits scientific and technological potential. However, to achieve highly efficient up-conversion and good temperature sensing performance from doped disordered glass matrix has led to limited success. Here, we report a nano-structured NaY2F7:Yb3+/Tm3+ glass ceramic for intense up-conversion in the first bio-window and sensitive optical response on temperature. Evidenced by detailed structural and optical characterization, the incorporation of Yb3+/Tm3+ into NaY2F7 nano-crystals results in the greatly enhanced and long-lived photoluminescence with noteworthy Stark splitting. More interestingly, the emission intensity ratio of thermally coupled 3F2,3 → 3H6 and 1G4 → 3F4 transition of Tm3+ is highly temperature dependent and repeatable due the protection of silicate glass network. Thus, NaY2F7:Yb3+/Tm3+ glass ceramic shows excellent temperature sensing performances, including high sensitivity, and excellent repeatability. In particular, the maximal relative and absolute sensitivity reach 1.63 %K−1 (415 K) and 10.01 %K−1 (567 K), respectively. These results reveal that Yb3+/Tm3+ co-doped NaY2F7 GC could be promising in the application of up-converting materials for high performance optical temperature sensor. •Highly transparent bulk NaY2F7:Yb3+/Tm3+ glass ceramic was successfully manufactured.•The formation of NaY2F7 nano-crystals and the enrichment of Yb/Tm into nano-crystals were confirmed.•SR-MAX reaches 1.63 %K−1 (415 K) and SA-MAX is 10.01 %K−1 (567 K).•NaY2F7:Yb3+/Tm3+ glass ceramic could be potential candidate for highly sensitive optical thermometry.